1 + a + 3 b + 9 c + 3 a b + 9 a c + 2 7 b c + 2 7 a b c = ?
Given that a = 9 9 9 , b = 3 3 3 , and c = 1 1 1 , evaluate the above sum.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Notice that b = 3 a and c = 9 a . Substituting in to the formula yields,
1 + a + 3 3 a + 9 9 a + 3 a 3 a + 9 a 9 a + 2 7 3 a 9 a + 2 7 a 3 a 9 a
= 1 + a + a + a + a 2 + a 2 + a 2 + a 3
= 1 + 3 a + 3 a 2 + a 3
Notice that coefficients make up the 4th row of Pascal's Triangle, meaning this expression factors into the cube of a binomial. Thus, we can write,
1 + 3 a + 3 a 2 + a 3 = ( 1 + a ) 3
We can now substitute in the given value of a = 9 9 9 to find ( 1 + 9 9 9 ) 3 = ( 1 0 0 0 ) 3 = 1 , 0 0 0 , 0 0 0 , 0 0 0
Problem Loading...
Note Loading...
Set Loading...
Given that a = 9 9 9 , b = 3 3 3 , and c = 1 1 1 , implies that a = 3 b = 9 c .
S = 1 + a + 3 b + 9 c + 3 a b + 9 a c + 2 7 b c + 2 7 a b c = 1 + a + a + a + a 2 + a 2 + a 2 + a 3 = 1 + 3 a + 3 a 2 + a 3 − ( 1 + a ) 3 = ( 1 + 9 9 9 ) 3 = 1 0 0 0 3 = 1 0 0 0 0 0 0 0 0 0